Value addtion of locally adapted underutilized crops - Sharma, Neetu; Dogra, Vishal; Kumar, Deep (Indian Farming, 2018)
The result concludes the advantages offered by the underutilized and neglected crops in enhancing the nutritional security of local communities and enhancing their income though this value addition venture. The unique strength of certain underutilized and neglected crops in their rich and favourable nutritional composition and product development offers uncommon opportunities for income generation to the farmers, in particular the farm-women.